Regulatory approaches for genome edited agricultural plants in select countries and jurisdictions around the world - Entine, Jon; Felipe, Maria Sueli S.; Groenewald, Jan-Hendrik; Kershen, Drew L.; Lema, Martin; McHughen, Alan; Nepomuceno, Alexandre Lima; Ohsawa, Ryo; Ordonio, Reynante L.; Parrott, Wayne A.; Quemada, Hector; Ramage, Carl; et al. (Springer, 2021)
Genome editing in agriculture and food is leading to new, improved crops and other products. Depending on the regulatory approach taken in each country or region, commercialization of these crops and products may or may not require approval from the respective regulatory authorities. This paper describes the regulatory landscape governing genome edited agriculture and food products in a selection of countries and regions.